Emma Goldman: Portrait of a rebel woman. - Ganguli, B.N. (Bombay Allied Publishers Private Limited, 1979)
The Book Recounts The Life History Of A Little Known Rebel. Focussing On Emma`S Struggle To Solve Her Own Specific Existential Problem Of Bondage As A Woman, The Study Shows How This Struggle Becomes Coeval With The Struggle For Women`S Liberation In Particular. Condition Good.
Keywords: Sociology- Emma Goldman; Sociology- Women's liberation; Sociology- Women- Violence